Peran Ulama dalam Persepektif Institusi Pendidikan Agama Islam - Abdul Muid (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
Ulema should not be underestimated in its mission as the heir to the Prophet, therefore clerics occupy seats were very respectable in the eyes of God SWT.dan human eyes. Position these scholars, not based on the appointment of a number of officials, but Ulama more as the heir to the Prophet's Mission and Vision have guided mankind and enforce commanding the good Nahi unjust. It reminds people to submissive and obedient to the religious scholars, where community ties and Ulama are fused. Because the Ulama in the State structure highly anticipated advice to guide the values of truth and justice. For Umara, is a manager in the structure of the State should not be rammed signs the values of truth, justice, prosperity in its mission to achieve a just and welfare state. In achieving its mission and vision, the cleric's advice is vital in order to uphold the dignity of justice. Umara should not be arrogant, arbitrary to the Ulema, especially chided, because The real Ulama are the inheritors of the Prophet's knowledge. Moreover, scholars in achieving his message to spread the values of religious education in order to drive the Ummah to the road of truth and justice in society.